فعالية استيراتيجية فرزالبطاقة وفراق الانجاز الطلال مؤسسا على التعلم السياق لترقية نتيجة درس الصرف لطلبة الفصل الثالث بكلية المعلمات الإسلامية معهد دار السلام كونتور - Hilma, Fanni; Subakir, Fairuz; Zarfa, Hazrati (Al-Fakkaar, 2024)
Third grade students of KMI Pondok Modern Darussalam Gontor experience learning difficulties and boredom in learning Shorof, which causes a decrease in learning motivation and low learning outcomes. Research Objective To study the effectiveness of contextual learning-based educational strategies compared to conventional learning methods in teaching Shorof material in the third grade of KMI Gontor. This study used a quantitative approach with a true experimental method and post-test only design. The research population was all third grade KMI students of Pondok Modern Darussalam Gontor which amounted to 276 students. The sample was taken using Stratified Random Sampling technique and divided into three groups: experimental group with Card Sort strategy, control group 1 with STAD strategy, and control group 2 with conventional method. Data were analyzed using descriptive statistical analysis, Shapiro-Wilk normality test, homogeneity test, Kruskal-Wallis test, and Mann-Whitney test. Research Results: There was a significant difference between the three groups (p = 0.001 < 0.05). Card Sort group obtained the highest mean score (7.93), followed by STAD (7.53), and conventional (6.26). There was no significant difference between Card Sort and STAD (p = 0.378 > 0.05). Card Sort was more effective than conventional method (p = 0.001 < 0.05) with an average difference of 1.67. STAD is more effective than conventional method (p = 0.007 < 0.05) with a mean difference of 1.67. STAD is more effective than the conventional method (p = 0.007 < 0.05) with an average difference of 1.27. Contextual learning strategies (Card Sort and STAD) proved to be more effective in improving Shorof learning outcomes than conventional methods.